Orthopaedic manual physical therapy for post-stroke shoulder pain: two case reports including clinical assessments and participants’ experiences - Ingrid Lindgren; Arne G. Lindgren; Håkan Carlsson; Tobias Lundgren; Christina Brogårdh (Journal of Rehabilitation Medicine - Clinical Communications)
Objective: To descriptively evaluate Orthopaedic Manual Physical Therapy – a novel intervention for post-stroke shoulder pain – by use of clinical assessments and the participants’ experiences.